2011
DOI: 10.1111/j.1360-0443.2011.03566.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological dysregulation, white matter disorganization and substance use disorders in adolescence

Abstract: Aims Adolescents with substance use disorders (SUD) have difficulties with cognitive, behavioral and affective regulation. White matter (WM) disorganization has been observed in adolescents with SUD and may be related to psychological dysregulation. This study compared adolescents with SUD and control adolescents to investigate relationships among psychological dysregulation, WM disorganization, and SUD symptoms. Design Cross-sectional observation. Setting Adolescents with SUD were recruited from SUD treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 66 publications
4
62
1
2
Order By: Relevance
“…However, in this sample, alcohol use during the interscan interval predicted reduced white matter integrity while cannabis did not. With only one exception (DeLisi et al, 2006), several studies have now reported reduced white matter quality in several PFC, limbic, parietal and cerebellar tracts in young cannabis users after controlling for alcohol use (Arnone et al, 2008; Ashtari et al, 2009; Bava et al, 2009; Clark et al, 2012; Gruber et al, 2011; 2013). Additional research disentangling the unique effects of alcohol versus cannabis on white matter integrity is needed.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this sample, alcohol use during the interscan interval predicted reduced white matter integrity while cannabis did not. With only one exception (DeLisi et al, 2006), several studies have now reported reduced white matter quality in several PFC, limbic, parietal and cerebellar tracts in young cannabis users after controlling for alcohol use (Arnone et al, 2008; Ashtari et al, 2009; Bava et al, 2009; Clark et al, 2012; Gruber et al, 2011; 2013). Additional research disentangling the unique effects of alcohol versus cannabis on white matter integrity is needed.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
“…Additional research disentangling the unique effects of alcohol versus cannabis on white matter integrity is needed. In a study examining the relationship between psychological dysregulation, white matter integrity and substance (including cannabis) use in teens, Clark et al, (2012) tested mediation models and concluded that poorer white matter quality in frontoparietal networks was both a risk factor for psychological dysregulation and CUD-related symptoms, and a result of cannabis use.…”
Section: Impacts Of Regular Cannabis Use On Neurocognition In Teenmentioning
confidence: 99%
See 1 more Smart Citation
“…Youth who completed baseline were approached to participate in a neuroimaging protocol (Thatcher et al, 2010; Chung et al, 2011; Clark et al, 2012; Chung et al, 2013), which was approved by the university’s Institutional Review Board. Youth were excluded from imaging based on standard restrictions (e.g., unremovable metal in the body), and a history of brain injury or concussion.…”
Section: Methodsmentioning
confidence: 99%
“…Image processing has been detailed elsewhere (Clark et al, 2012; Chung et al, 2013). Briefly, FreeSurfer (Dale et al, 1999; Fischl et al, 2002, Fischl et al, 2004) was used to create gray and white matter regions of interest (ROIs) based on standard parcellation units (Desikan et al, 2006).…”
Section: Methodsmentioning
confidence: 99%